Within‐island diversification underlies parachuting frog (Rhacophorus) species accumulation on the Sunda Shelf. (24th January 2018) - O'Connell, Kyle A.; Smart, Utpal; Smith, Eric N.; Hamidy, Amir; Kurniawan, Nia; Fujita, Matthew K.
Abstract: Aim: This study seeks to understand the geological and climatological processes that have promoted biodiversity on the Sunda Shelf in Southeast Asia. Using the parachuting frog genus Rhacophorus, we estimate divergence times and quantify the respective contributions of between and within‐island diversification to species richness and endemism. Location: East and Southeast Asia, the Sunda Shelf. Methods: We generated a concatenated mitochondrial and nuclear DNA sequence alignment for 40 species of Rhacophorus . We estimated phylogenetic relationships and divergence times, constructed lineage‐through‐time (LTT) plots and reconstructed ancestral ranges. Results: We found that Rhacophorus originated 33.0 Ma (95% HPD 27.0–38.0 Ma), and that the diversification rate slowed towards the present. Dispersal was important in early Rhacophorus evolution, but subsequent in situ diversification produced most species diversity on Sumatra and Borneo. Clades that diversified via in situ processes contained higher proportions of endemic species. Main conclusions: Species diversification on the Sunda Shelf is ancient and has occurred slowly. Both dispersal and in situ diversification have promoted Sundaland species accumulation, but within‐island phylogenesis has produced a greater proportion of endemic species on Sumatra and Borneo. Species richness and endemism are most influenced by the size of an island, rather than connectivity.